Space Systems Emerging Technologies and Operations - Nichols, Randall K.; Mumm, Hans C.; Lonstein, Wayne D.; Ryan, Julie J.C.H; Carter, Candice M. (Open textbook library., 2024)
SPACE SYSTEMS: EMERGING TECHNOLOGIES AND OPERATIONS (SSETO) is our seventh textbook in a series covering the world of UASs / CUAS / UUVs. SSETO takes on a new purview of SPACE. UASs (Drones) have a maximum altitude of about 33,000 ft (10 km) because rotating rotors become physically limiting. (Nichols R. et al., 2019) Between 400 ft and 33,000 ft is in the purview of DREAMERS. In the DREAMERS region, Space has its most interesting technological emergence. We see emerging technologies and operations that may have profound effects on humanity. This is the mission our book addresses. We look at the Dreamer region from three perspectives: 1) a Military view where intelligence, jamming, spoofing, advanced materials, and hypersonics are in play; 2) the Operational Dreamer Region; which includes Space-based platform vulnerabilities, trash, disaster recovery management, A.I., manufacturing, and extended reality; and 3) the Humanitarian Use of Space technologies; which includes precision agriculture wildlife tracking, fire risk zone identification, and improving the global food supply and cattle management. State-of-the-Art research by a team of fifteen SMEs is incorporated into our book. We trust you will enjoy reading it as much as we have in its writing. There is hope for the future.